A Square or a Crossroads? The Vernacular in Urban Policy of Moscow Classicism - Klimenko, Julia (project baikal, 2019)
In the history of Moscow classicism there were many unsuccessful attempts to create regular squares. In the modern historical center of Moscow there are a lot of squares, which are actually intersections or carfaxes. The article analyzes the architectural policies from Catherine II to Alexander I. The study of the discovered archival documents makes it possible to compare them with the experience of Western European urban planning of the age of Enlightenment.